Academic Management — The Case for Challenge - Dowdeswell, W. H.; Good, Harold M. (Canadian Journal of Higher Education, 1982)
An examination was made of how well certain units involved in managing the teaching-learning organizations of universities work. Criteria for acceptable operation involved clarity of communication, matches between objectives at different levels of the administrative hierarchy, matches between objectives and methods, and rationality of approach to cost-effectiveness. Significant defects were found in relation to each of these criteria suggesting that both selection and training of staff at all levels are now, to some degree, deficient. Inefficiencies relating to poor information gathering, and poor communication were identified as was unnecessary duplication between faculty and department organizations.